2020
DOI: 10.1186/s12933-020-01138-w
|View full text |Cite
|
Sign up to set email alerts
|

The additive effects of type 2 diabetes mellitus on left ventricular deformation and myocardial perfusion in essential hypertension: a 3.0 T cardiac magnetic resonance study

Abstract: Background Type 2 diabetes mellitus (T2DM) increases the risks of heart failure and mortality in patients with hypertension, however the underlying mechanism is unclear. This study aims to investigate the impact of coexisting T2DM on left ventricular (LV) deformation and myocardial perfusion in hypertensive individuals. Materials and methods Seventy hypertensive patients without T2DM [HTN(T2DM−)], forty patients with T2DM [HTN(T2DM+)] and 37 age- and sex-matched controls underwent cardiac magnetic resonance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Essential hypertension and T2DM are two common chronic diseases. T2DM can aggravate LV diastolic dysfunction in patients with essential hypertension [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essential hypertension and T2DM are two common chronic diseases. T2DM can aggravate LV diastolic dysfunction in patients with essential hypertension [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the adverse effect of DM on LV systolic function are not fully understood. HFpEF comorbid with DM could induce a broad context of metabolic disorder, oxidative stress, and a systemic inflammatory state, resulting in excitation-contraction coupling impairment, extracellular matrix fibrosis, and microvasculature dysfunction, thereby promoting myocardial contractility impairment [ 3 , 23 , 26 ]. Based on the observation in our study that DM has a greater adverse effect on LV contractility in women than in men, the decline in the estrogen level at menopause together with the presence of DM may be responsible for this difference [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, microvascular abnormalities are an important disorder in both conditions with certain common pathological changes: endothelial dysfunction, microvascular remodeling and rarefaction ( 20 ). Some previous studies revealed no obvious difference in the resting myocardial perfusion between hypertensive and normotensive subjects ( 21 , 22 ), while other studies reported significantly increased resting myocardial perfusion in hypertensive patients due to an adaptive mechanism ( 23 , 24 ). Our results showed slightly increased resting myocardial perfusion in hypertensive patients without obesity compared with controls, but this difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 86%